Evidence on the Convergence of Per Capita Income: A Comparison of Founder Members of the Association of South East Asian Nations and the South Asian Association of Regional Cooperation. (3rd February 2013) - Jayanthakumaran, Kankesu; Lee, Shao‐Wei
Abstract This paper investigates the per capita income convergence patterns of a set of Association of South East Asian Nations (ASEAN) and South Asian Association of Regional Cooperation (SAARC) countries. We obtained a time‐series analysis for stochastic convergence by applying unit‐root tests in the presence of two endogenously‐determined structural breaks. We then supplemented the results by tests that produced evidence for β convergence. The evidence shows that the relative per capita income series of ASEAN‐5 countries were consistent with stochastic convergence and β convergence, but this was not found for SAARC‐5 countries. For the ASEAN‐5 countries, the structural breaks associated with the world oil crisis and the Asian crisis impacted heavily on the convergence/divergence process.